Markers of inflammation in patients with generalized anxiety disorder - Yildiz, Sevler; Kilicaslan, Asli Kazgan; Emir, Burcu Sirlier; Tabara, Muhammed Fatih; Kurt, Osman; Sehlikoglu, Seyma; Ugur, Kerim (Cukurova Univ, Fac Medicine, 2024)
Purpose: The aim of this study was to analyze the systemic immune response index, systemic immune inflammation platelet/HDL, and monocyte/HDL ratio, used as inflammatory markers in patients with generalized anxiety Materials and Methods: A total of 864 participants, including 432 healthy controls and 432 patients diagnosed with GAD, were included in this study. High-density lymphocyte, and platelet counts; systemic inflammatory calculated. contributing to both diagnosis and management.
Keywords: Generalized anxiety disorder; SIRI; SII; NHR; LHR; MHR; PHR; inflammation